1978
DOI: 10.1128/jb.133.3.1478-1483.1978
|View full text |Cite
|
Sign up to set email alerts
|

New major outer membrane proteins found in an Escherichia coli tolF mutant resistant to bacteriophage TuIb

Abstract: Cell envelopes prepared from an Escherichia coli tolF strain selected as resistant to phage TuIb contained a new major outer membrane protein related to outer membrane proteins la and Ib. The strain that produces this protein is a tolF par double mutant but contains an additional mutation leading to the production of the new major outer membrane protein. Antibiotic sensitivity lost as a result of the tolF mutation is regained in strains that contain the new major outer membrane protein. This indicates that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
38
2

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 25 publications
2
38
2
Order By: Relevance
“…From this experiment it was concluded that there was no crossreactivity between the new membrane proteins and antiserum against protein la + lb. The reason for the discrepancy between our results and those of Foulds and Chai (9) is not known at present. DISCUSSION The results presented here indicate that at least three distinct genetic loci control some aspect of the production by E. coli K-12 of new major outer membrane proteins which are not normally expressed in wild-type strains.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…From this experiment it was concluded that there was no crossreactivity between the new membrane proteins and antiserum against protein la + lb. The reason for the discrepancy between our results and those of Foulds and Chai (9) is not known at present. DISCUSSION The results presented here indicate that at least three distinct genetic loci control some aspect of the production by E. coli K-12 of new major outer membrane proteins which are not normally expressed in wild-type strains.…”
Section: Resultscontrasting
confidence: 99%
“…However, only CS483 (NmpC+) was measurably more sensitive to colicin A. The Nmp+ strains remained fully resistant to colicins K, L, S4, and X, and remained sensitive to colicins B, D, G, H, Ia, Ib, M, Si, and V. We also examined strain JF720, a derivative of the Nmp+ strain described by Foulds and Chai (9), and found this strain to be almost fully sensitive to colicins E2 and E3, and therefore similar to our NmpA+ and NmpB+ mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other peptidoglyean-assoeiated proteins have been reported. One was found in cells lysogenized by phage PA2 [ 11 ] and the others were found in mutants having defects in 0-8 and/or 0-9 synthesis [12][13][14][15]. Judging from the migration position in a polyacrylamide gel, it is clear that neither O-13 nor O-14 is identical with any one of these peptidoglyean associated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently described one such revertant, strain JF694 (14). Strain JF694 is a tolF par strain that carries a third mutation which results in the appearance of a new major outer membrane protein we have called protein E (14). Other laboratories have reported strains that produce a similar new major outer membrane protein.…”
mentioning
confidence: 99%